Relationship of Organizational Culture and Leadership Style towards Change Management in the Implementation of Good Corporate Governance - puspitasari, dwi ida; Suwanto, Suwanto; Supriyatno, Andik (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
Good corporate governance is a system that regulates and controls the organization to create value added for all stakeholders. So the purpose of this study is to conduct research on the relationship between organizational culture and leadership style to change management in the implementation of good corporate governance at RSIA Jimmy Medika Borneo Samarinda. This research is a type of quantitative research using analytical observational studies with a cross-sectional design. The population in this study was all structural officials and functional officials of the entire installation at RSIA Jimmy Medika Borneo Samarinda. The total number of the population is 45 people. There is a relationship of Leadership, implementation, organizational culture with change management in the implementation of good corporate governance in rsia jimmy medika borneo Samarinda. Maintaining the organizational culture that has been formed at RSIA JMB and improving the organizational culture that is not good